1975
DOI: 10.1107/s0567740875008461
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorobis(4-methylpyridine)cobalt(II)

Abstract: Abstract. CoCI2(NCsH4.CH3)2, monoclinic, P2x/n, a= 5.70 (1), b=10.16 (1), c=24.36 (2) A,, fl=92.4 (1) °, Z=4, De= 1.49 g cm -3. C1-Co-CI= 121, N-Co-N= 107°; Co is tetrahedrally coordinated. The molecular packing differs from that of the ZnCI2 and ZnBr2 analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…29 The intermolecular kinetic isotope effect for alkane C-H oxidation was determined by the competitive oxidation of cyclohexane and cyclohexane-dlz (k& = 2.?!). 30 This small intermolecular KIE is consistent with some,3i-33 but not all,34 studies for the oxidation of alkanes by MMO and is indicative of only a minor contribution from C-H bond breaking in the rate-determining step of substrate oxidation.…”
Section: N-melmsupporting
confidence: 70%
See 1 more Smart Citation
“…29 The intermolecular kinetic isotope effect for alkane C-H oxidation was determined by the competitive oxidation of cyclohexane and cyclohexane-dlz (k& = 2.?!). 30 This small intermolecular KIE is consistent with some,3i-33 but not all,34 studies for the oxidation of alkanes by MMO and is indicative of only a minor contribution from C-H bond breaking in the rate-determining step of substrate oxidation.…”
Section: N-melmsupporting
confidence: 70%
“…2) shows Co2+ to be tetrahedrally coordinated; the bond lengths and angles in the molecule are normal within the observed standard deviations of the few tetrahedral CoA2X, compounds that have been characterized and are different from the polymeric six-coordinate violet form of CoPy2C1, [24,29]. The somewhat shorter Co-Nl (2.004 A) and Co-N3 (2.007 A) bond lengths of 1 versus those reported for the 4-methylpyridine complex (2.03 and 2.06 A) reflect the greater basicity of the N-MeIm ligand (pK, = 7.06) versus 4-MePy (pK, = 5.25) [30]. However, the largest variations in the CoA2Cl, structures are observed to occur in the N-Co-N angles that appear to depend intimately on the stereochemical requirements of the nitrogen heterocycles.…”
Section: Solution and Solid-state Structure Of Co(n-meim)(ci)2 (1)mentioning
confidence: 96%
“…It is worth mentioning that except Co(3-pic) 2 Cl 2 exists as a six coordinated Co compound: dibromo-tetrakis(3-picoline)cobalt(II) [32]. The Co-N and Co-Cl bond lengths are compatible with those found in analogous compounds of 4-picoline [20], quinoline [21] and (8) 6,6¢-dimethyl-2,2¢-bipyridyl [22] and they are slightly shorter than those found in a polymeric form of a-Co(py) 2 Cl 2 (Co-N 2.14 Å ; Co-Cl 2.49 Å ) with cobalt(II) in the octahedral environment [3].…”
Section: Structural Descriptionmentioning
confidence: 61%
“…Structural studies of these compounds have shown them to be capable of polymerization whereby the cobalt atom assumes either an octahedral environment as highlighted by the violet-coloured Co(py) 2 Cl 2 compound [1][2][3], or a tetrahedral one displayed by the blue Co(py) 2 Cl 2 [1][2][3] and Co(4-pic) 2 Cl 2 [20] compounds. These results have shown that the structure of the compound is dependent on the nature of the pyridine ring substituent.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation